Assessment and Monitoring of Coagulation in Patients with COVID-19: A Review of Current Literature - Uzun, Günalp; Althaus, Karina; Hammer, Stefanie; Bakchoul, Tamam (Hämostaseologie, 2022)
Coagulation abnormalities are common in patients with COVID-19 and associated with high morbidity and mortality. It became a daily challenge to navigate through these abnormal laboratory findings and deliver the best possible treatment to the patients. The unique character of COVID-19-induced coagulopathy necessitates not only a dynamic follow-up of the patients in terms of hemostatic findings but also the introduction of new diagnostic methods to determine the overall function of the coagulation system in real time. After the recognition of the high risk of thromboembolism in COVID-19, several professional societies published their recommendations regarding anticoagulation in patients with COVID-19. This review summarizes common hemostatic findings in COVID-19 patients and presents the societal recommendations regarding the use of coagulation laboratory findings in clinical decision-making. Although several studies have investigated coagulation parameters in patients with COVID-19, the methodological shortcomings of published studies as well as the differences in employed anticoagulation regimens that have changed over time, depending on national and international guidelines, limit the applicability of these findings in other clinical settings. Accordingly, evidence-based recommendations for diagnostics during acute COVID-19 infection are still lacking. Future studies should verify the role of coagulation parameters as well as viscoelastic methods in the management of patients with COVID-19.
Keywords: coagulopathy; D-dimer; thrombosis; fibrinolysis